Sistem PENERAPAN SISTEM PEMBELAJARAN DAN PUSTAKA ONLINE MENUJU PENDIDIKAN YANG MODERN DI ERA INDUSTRI 4.0 PADA PESANTREN CILELES, JATINANGOR: Sistemtem pembelajaran online - Keni Kaniawati keni; Fansuri Munawar; Asep Anwar (Jurnal Ilmiah Teknologi Infomasi Terapan, 2022)
The objectives of implementing community service activities for the independent learning program for independent campuses carried out by the Al-Istiqomah Islamic Boarding School in Cileles Jatinangor Regency are: 1) Contribute to the Al-Istiqomah Islamic Boarding School in Cileles Jatinangor for the problems they face; 2) Provide training, simulation, assistance related to the problems faced, 3) Help develop the e-learning digitization process for the problems encountered, both for the learning system and online library. The implementation methods used to overcome the problems faced by partners are observation of needs, planning and data collection, implementation of hosting and moodle installations, system evaluation and socialization of learning systems. With the implementation of this activity there are changes, the Al-Istiqomah Islamic Boarding School has an independent learning management system website, a better understanding of online learning systems and libraries, and better abilities of ustadz and students in using online learning systems and libraries.Keywords: online learning system, online library, Islamic boarding school